From Sensors to Robots: Learning Instrumentation Physics Technology and Computer Vision for Students of SMA IT Daarul ‘Ilmi Bandar Lampung - Surya Prihanto; Yusril Al Fath; Ayu Aprilia; Ahmad Faruq Abdurrahman; Raihan Rafii; Dafa Ariwinadi; Satrio; Muhammad Ajie Wahyudi (Society : Jurnal Pengabdian Masyarakat, 2026)
This community service activity was motivated by students’ limited understanding of instrumentation physics and the lack of exposure to the application of technologies such as sensors, microcontrollers, and computer vision in both daily life and industry, including related study prospects. This activity aims to enhance students’ understanding and interest in instrumentation physics through socialization and technology-based demonstrations. The implementation methods included pre-tests and post-tests to measure improvements in students’ understanding, material delivery sessions, and demonstrations of various technologies, such as sensor-based water quality monitoring systems, microcontroller-based automatic door systems, a 4-DOF robotic arm, and a Python-based computer vision system for hand detection.The results showed an improvement in students’ understanding, as indicated by an increase in the average pre-test score (x = 2.63) to the post-test score (x' = 3.31), with a mean gain of (Δx = 0.68). In addition, students’ interest in pursuing further studies in instrumentation physics also increased after the activity.Overall, this activity proved to be effective in providing students with interactive, contextual, and application-oriented learning experiences.